Cyophiobiolins A-D, ophiobolin sestertepenoids from Cytospora rhizophorae. (November 2022) - Zhang, Yanjiang; Liu, Hongxin; Chen, Yuchan; Lu, Xiuxiang; Liu, Zhaoming; Tan, Haibo; Zhang, Weimin
Abstract: Cyophiobiolins A-D, four unreported ophiobolin-type sesterterpenoids, were isolated from Cytospora rhizophorae A761, an endophytic fungus from Gynochthodes officinalis . The structures of these undescribed compounds were fully characterized on the basis of extensively spectroscopic data (1D, 2D NMR and HRESIMS) and single-crystal X-ray diffraction analyses. Moreover, cyophiobiolins A-D were evaluated for in vitro cytotoxic, anti-inflammatory, and antibacterial activities. Cyophiobiolins A-B showed inhibitory potency against lipopolysaccharide (LPS)-induced oxide production with IC50 values of 66.3 μM and 53.3 μM, respectively. Graphical abstract: Cyophiobiolins A-D, four unreported ophiobolin-type sesterterpenoids, were isolated from Cytospora rhizophorae A761, an endophytic fungus from Gynochthodes officinalis . Image 1 Highlights: Four unreported ophiobolins were isolated from Cytospora rhizophorae A761. This is the first report of ophiobolin sestertepenoids type in Cytospora. Cyophiobiolins A-B displayed anti-inflammatory activity without cytotoxicity.